Primary Productivity in the Mid-Atlantic Bight: Is the Shelf Break a Location of Enhanced Productivity? - Ma, Jiejie; Smith, Walker O. (Frontiers in Marine Science, 2022)
Estimates of primary production represent the input of carbon into food webs, as well as the initial step in the biological pump. For the past 60 years, much of the productivity information has been obtained using measurements of 14C-bicarbonate removal during simulated in situ incubations. However, such measurements often do not reflect the complexity of the environment, and also suffer from uncertainties, biases and limitations. A vertically resolved bio-optical model has been used to estimate productivity based on profiles commonly assessed in oceanographic investigations, but comparisons with simultaneous measurements of 14C-uptake are limited. We conducted three cruises off the coast of New England that included sampling continental shelf waters, the shelf-break region, and deeper waters at scales of 7 km, all of which had productivity estimated by a vertically resolved productivity model as well as by traditional 14C-uptake measurements using simulated in situ techniques. We found that the vertically resolved bio-optical model gave results that appear to be more robust and resolved productivity at smaller vertical and horizontal scales, and seem less biased by some of the uncertainties in 14C-uptake measurements. Both estimates suggest that the New England waters are highly productive due to a variety of biological and physical processes occurring at different times of the year, but there was no consistent stimulation at the shelf break over the time scales of these estimates.